Ginger extract modulates the expression of IL-12 and TGF-β in the central nervous system and serum of mice with experimental autoimmune encephalomyelitis - Abdollah Jafarzadeh; Rayhane Ahangar-Parvin; Maryam Nemati; Zahra Taghipour; Ali Shamsizadeh; Fatemeh Ayoobi; Zuhair Hassan (Mashhad University of Medical Sciences, 2017)
Objective: The main function of IL-12 is differentiation of naive T cells intoTh1 cells and TGF-β is a powerful immunoregulatory cytokine. The immunomodulatory and anti-inflammatory properties of ginger have also been reported in some studies. The aim of this study was to evaluate the effects of ginger extract on the expression of IL-12 and TGF-β in a model of experimental autoimmune encephalomyelitis (EAE).Materials and Methods: EAE was induced in C57BL/6 mice by immunization with myelin oligodendroglial glycoprotein emulsified in complete Freund's adjuvant. The mice were administered intra-peritoneally with ginger extracts or PBS, from day +3 to +30. On day 31, mice were scarified and the expression of IL-12 and TGF-β mRNA in the spinal cord were determined by using real time-PCR. The serum levels of cytokines were measured by ELISA.Results: In PBS-treated EAE mice, the expression of IL-12 P35 and IL-12 P40 mRNA in the CNS and the mean serum levels of IL-12 were significantly higher than those of healthy group (p